AGED And The CORPORAL IMAGE (Fiep Bulletin - online, 2015)
Our focus of investigation decays on the transformations of the body in the oldness. Transformations that can be concret (anatomic and physiological) and symbolic or representational. The body as fundamental reality in the determination of the personal or social identity is a decisive factor to people's life style. In the old-age, this life style goes necessarily through many changes; some of them because of functional incapacities bore for the age. But old-age cannot be seeing or felt just as senility or a period of deficiencies that foregoes death. In this context, the concept of body image as a social and psychological construction that reflects faces is approached: an auto-image and an image that society has on the body of old-aged people. Confronting these two sides, there is an old-age that needs to be thought from the deconstruction of valid models of health linked to traditional medicine, of biomedical models, connected to several stereotypes and reductions. But how this old person lives, how he or she forms the body image along the trajectory into society? Before the possible answers found in this narrative, we can infer to the discussion of what would be the quality of life in the old-age, what, on the other hand, takes us to the discussion of what is a healthy life.The body image, therefore, assumes a focus of meanings to be explained, beyond the natural and physical limits of the skin, allowing us to describe the changes that occur in the oldness, in the acquisition and improvement of the human being. In this perspective, quality of life, besides attitude, assumes the value of growing challenge for understanding the actual emphasis offered in the quick solutions to caring old-aged people. It is proper, therefore, in this context, to think again about the managing of these solutions on the attention to the body including the physical presence of other people. In the awakening of this new conscience, the narrative assumes, in this investigation, the method of research. Nothing is more convenient than having how to insert the body image based on the cognitive stock of knowledge generated by the stories, lending its cultural mark to the organization of life experiences.
Keywords: Body; Quality of Life; Old-Aged People; Oldness.